Discrete Element Modelling of the dynamics of a Self-Rotating Object in dense Granular Media. Issue 5 (May 2021) - Liu, Ping; Zou, Xuan; zhou, Jingyuan; Tang, Wenhui; Ran, Xianwen
Abstract: Many reptiles can move significant distances through sand or many seeds drill out soil during germination by rotating their bodies. Inspired by the biological behaviour and challenged by the absence of physical mechanism for the locomotion in granular materials, we developed a numerical study of a self-excited spherical intruder in a granular bed under gravity, using discrete element method. In simulation, the intruder was rotated around x-axis with different friction coefficient μ and rotation angular velocity ω . We find that the space motion of intruder is sensitive to these two parameters. It moves farther in the Z + direction with the increase of μ and ω . and there emerges opposite movement in the Y direction with the change of ω . We analysed the physical mechanisms governing these motions and proposed two qualitative theory: the tangential force raises with the increase of ω . which causes the intruder to lift faster; the competition mechanism between friction effect and squeezing effect leads to the motion differentiation of intruder in the Y direction. These results of this study pave the way for the design of an efficient bio-inspired robot moving within seabed or desert according to this mode of locomotion.